Designed genotoxicity profiling detects genotoxic compounds in staple food such as healthy oils. (15th May 2023) - Morlock, Gertrud E.; Meyer, Daniel
Highlights: New genotoxicity profiling was developed to analyze healthy oils for genotoxins. Healthy oils containing unsaturated fatty acids were shown to be genotoxic. Detoxification of genotoxins in healthy oils was demonstrated for the first time. Since not S9-metabolized, topical application of healthy oils is deemed harmful. Genotoxic effects were differentiated from opposing responses and cytotoxic effects. Abstract: Current techniques used in food analysis overlook genotoxic compounds. This urgently calls for a paradigm shift in analytics towards non-target planar genotoxicity profiling that can detect genotoxins. Up to eight different genotoxins ( i.e., genotoxic compound zones) have been detected in 33 oils used for healthy diets. A comparison of fresh oils with oils stored open and closed for one month identified genotoxic degradation products. Characterization of genotoxic zones via high-resolution mass spectrometry revealed oxidized linolenic acid as a source of genotoxicity in all samples. Detoxification via on-surface S9 liver metabolization was investigated, which showed a reduction in most, but not all, genotoxins. Food, feed, dietary supplements, and cosmetics as sources of genotoxicity can now be identified by combining separation, effect detection and optionally simulated metabolization on the same surface. The application of the planar genotoxicity profiling will improve the understanding on food and its impact as well as risk assessment and derived recommendations.